No time for powers - Donati, Donatella (2018)
This thesis focuses on two related though different topics: first, the metaphysics of dispositions; second, the relation between dispositionalism and time. For this reason, the thesis is divided in two main parts: the first part concerns the first topic, and the second part concerns the second. The aim of the project is to argue that dispositionalism faces two different problems: first, there is no viable metaphysics for dispositional properties; second, there is no viable theory of time that can fit in a dispositional framework.